Exposure assessment of indoor fine particulate matter 2.5 (PM2.5) in bound to heavy metals among shop in urban area of Kuantan - Aida Khairani, Ariffin (2018)
Heavy metals may come from many different sources to the urbanized area. One of the most important heavy metals source is vehicle emission. The concentrations of several types of heavy metals were measured in indoor dust from five different shop vendors at two different roads which is Jalan Mahkota and Jalan Besar in urban area at Kuantan to illustrate their concentration and their characterization which is chemically and physically. The levels of five types heavy metals in indoor environment shows that Lead (Pb) was the highest concentration compared to four heavy metals which is Cadmium (Cd), Chromium (Cr), Copper (Cu) and Zinc (Zn). Moreover, the study of heavy metals in indoor is important due to their critical effects on human specifically in indoor because 90% most of times people spend in indoor. Furthermore, potential determinants factors of indoor air quality in shops vendors along an urban street also was determined which is air velocity, temperature and relative humidity using instrument which is Anaemometer. The samples collection, preparation and analysis were carried out using standard procedures. Inductively Coupled Plasma Mass Spectrometry (ICP-MS) was used to determine the concentration of heavy metals at the surface of Teflon filter paper. The average of concentration value of Cd, Cr, Cu, Pb and Zn are 0.35 ppb, 19.03 ppb, 6.79 ppb, 36.53 ppb and 0.37 ppb respectively.